2021
DOI: 10.1111/febs.15683
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic activity of splenic macrophages is enhanced and accompanied by cytosolic alkalinization in TRPM7 kinase‐dead mice

Abstract: Transient receptor potential melastatin 7 (TRPM7) is a unique protein functioning as a cation channel as well as a serine/threonine kinase and is highly expressed in immune cells such as lymphocytes and macrophages. TRPM7 kinase-dead (KD) mouse model has been used to investigate the role of this protein in immune cells; these animals display moderate splenomegaly and ectopic hemopoiesis. The basal TRPM7 current magnitudes in peritoneal macrophages isolated from KD mice were higher; however, the maximum current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…This difference may be due to the dependence on TRPM7 kinase resting pH in HEK cells. We recently showed that in murine macrophages isolated from TRPM7 K1646R kinase-dead mice, the pH is more alkaline than in WT, suggesting that kinase activity may make pH i more acidic ( Beesetty et al, 2021 ). WT TRPM7 overexpressing HEK cells also respond readily to acidification in propionate and 2-APB ( Zhelay et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be due to the dependence on TRPM7 kinase resting pH in HEK cells. We recently showed that in murine macrophages isolated from TRPM7 K1646R kinase-dead mice, the pH is more alkaline than in WT, suggesting that kinase activity may make pH i more acidic ( Beesetty et al, 2021 ). WT TRPM7 overexpressing HEK cells also respond readily to acidification in propionate and 2-APB ( Zhelay et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to Mg 2+ , other metal ions, polyamines and protons, are also inhibitory ( Kozak and Cahalan, 2003 ; Kozak et al, 2005 ; Chokshi et al, 2012b ; Zhelay et al, 2018 ). Channel inhibition by Mg 2+ and protons does not depend on the kinase activity ( Kozak et al, 2005 ; Matsushita et al, 2005 ; Beesetty et al, 2021 ). TRPM7 channels have been implicated in cellular and body Mg 2+ homeostasis ( Zou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…Subsequently, macrophages were washed and fluorescent latex beads (Cat. #15702-10 Fluoresbrite ® Microparticles, Polysciences) were added to the wells (100 beads/cell reconstituted in 1x PBS) ( 38 , 39 ). Afterwards, cells were kept at 37°C for 30 minutes while shaking.…”
Section: Methodsmentioning
confidence: 99%
“…The observation that both suppression and excessive activity of small G proteins impairs phagocytosis may be explained by the fact that the complete engulfment of large cargoes relies on both actin assembly and the subsequent rapid deactivation of G proteins and actin disassembly [ 117 ]. Finally, another recent work identified transient receptor potential melastatin 7 (TRPM7), a cation channel with kinase activity, as a suppressor of RPMs’ phagocytic activity through a mechanism that likely involves cytosolic alkalinization [ 118 ].…”
Section: Regulation Of the Erythrophagocytosis Ratementioning
confidence: 99%